أهمية إدارة الجودة الشاملة في تحسين جودة خدمة التعليم العالي (Rawafid Journal for Research and Studies, 2017)
ملخص الدراسة:يمثل التعليم العالي أهم دعائم تطوير المجتمعات البشرية وأدوات النهوض بها وذلك لما يحتله من مكانة في تهيئة وإعداد الأطر الفنية والعلمية المؤهلة لتحقيق التنمية الاقتصادية والاجتماعية، إضافة إلى دوره في صناعة المعرفة والعلم ونشرها، وإن اعتماد نظم الجودة في التعليم الجامعي ما هو إلا استجابة لمتطلبات المجتمع وتحفيز الإبداع وإجراء البحوث العلمية لتحقيق التنمية الشاملة خدمة للمجتمعالبشري. يأتي هذا المقال في مجال البحث حول تحسين جودة الخدمة التعليمية في حيث ، (Total Quality Management) ضوء مفهوم إدارة الجودة الشاملة يعد هذا المفهوم من المفاهيم الإدارية الحديثة والتي ظهرت نتيجة للمنافسة العالمية الشديدة بين مؤسسات الإنتاج: اليابانية والأمريكية والأوروبية، إذ تمكنت اليابان بفضل جودة منتجاتها من اكتساح الأسواق العالمية والفوز برضا المستهلكين حول العالم، جراء استخدام إدارة الجودة الشاملة في المؤسسات: الاقتصادية والصناعية والتكنولوجية والتجارية، وترجع فلسفة الجودة إلى العالم الأمريكي ديمنج والذي يسمي بأبي الجودة، ونظرا للنجاح الكبير الذي (Edward Deeming) حققه هذا النهج الإداري بدأ الاهتمام باستخدامه في المؤسسات التعليمية بدرجة متزا يدة. لقد أكدت العديد من الدراسات العالمية التي تبنت مفهوم إدارة الجودة الشاملة على أهمية ذلك النهج ونجاحه للحصول على منتج صناعي قادر على المنافسة في الأسواق العالمية، وكذلك الحصول على منتج تعليمي مناسب في المؤسسات التعليمية ألا وهو نوعية الطالب الخريج من تلك المؤسسات القادر على الإسهام بتنمية المجتمع بكافة المجالات بصورة فعالة.AbstractHigher education is the most important foundations for the development of human societies and their advancement to the position of prestige in the creation and preparation of technical and scientific frameworks for economic and social development. In addition to its role in knowledge, science and industry, and the adoption of quality systems in higher education is a response to the demands of society and to stimulate innovation and scientific research for the comprehensive development of human society.The intervention research on improving the quality of educational service in the light of the concept of TQM (Total Quality Management), which is the concept of modern management concepts, which have emerged as a result of strong global competition between production enterprises: Japanese, American, European, Japan, thanks to the quality of its products from sweep world markets and win the consent of consumers around the world, the use of total quality management in enterprises: Economic, industrial, technological, commercial, and returns us to the world quality philosophy Deming (Edward Deeming) called babe, and due to the great success achieved by this administrative policy began to be used in educational institutions increasingly.Many studies have confirmed that embraced the concept of total quality management on the importance of that approach and success for industrial product competitive in world markets, as well as getting a proper education in educational institutions is the quality of the student graduate from these institutions can contribute to community development in all fields.